Invisible Emmie - Libenson, Terri (New York, NY Balzer + Bray, an imprint of HarperCollinsPublishers, 2017)
This is the story of two totally different girls -- quiet, shy, artistic Emmie and popular, outgoing, athletic Katie -- and how their lives unexpectedly intersect one day, when an embarrassing note falls into the wrong hands. All the crushes, humiliation, boredom, and drama of middle school are compressed into one surprising day
English stories
Ages 8-12
1
Keywords: Bashfulness in children -- Comic books, strips, etc; Bashfulness in children -- Juvenile fiction; Bashfulness in children; Female friendship -- Comic books, strips, etc; Female friendship -- Juvenile fiction; Female friendship; Friendship -- Fiction; Girls -- Comic books, strips, etc; Girls -- Fiction; Girls -- Juvenile fiction; Girls; JUVENILE FICTION / Comics & Graphic Novels / Humorous; JUVENILE FICTION / Social Themes / Friendship; JUVENILE FICTION / Social Themes / Self-Esteem & Self-Reliance; Middle schools -- Comic books, strips, etc; Middle schools -- Fiction; Middle schools -- Juvenile fiction; Middle schools; Schools -- Comic books, strips, etc; Schools -- Juvenile fiction; Schools; Friendship -- Fiction; Girls -- Fiction; Graphic novels; Middle schools -- Fiction; Schools -- Fiction; Comic books, strips, etc; Fiction; Graphic novels; Graphic novels; Humorous fiction; Juvenile works; Graphic novels